Department classification in Peru by factor and accumulation analysis - Cruz-Saco, María Amparo (Universidad del Pacífico, 1995)
This study utilizes both factorial and cluster analysis techniques to lay out and categorize Peru's departments in decreasing order of development level. The findings show that the chief discrepancies arise in health-related variables. The demographic profile and industrialization indicators also figure prominently. The study confirms the hypothesis of the dual nature of Peruvian society and highlights the sharp differences between department groups according to level of industrialization and rural poverty. The more modern and industrialized Lima and Callao zone is contrasted with traditionally rural Andean region departments. On the premise that inter-regional equality should be one of the Peru's primary goals, it is a matter of urgency that economic policy incorporate fiscal and compensatory measures aimed at improving health standards and stimulating socio-economic development in file more depressed departments.